Tantangan, Harapan, dan Peluang Tadris Matematika dalam Mewujudkan Guru Matematika yang Islami,Profesional, dan Kompetitif - Mutia Mutia; Wiwin Arbaini Wahyuningsih (ARITHMETIC: Academic Journal of Math, 2019)
In line with the vision of the Mathematics Tadris Study Program at the IAIN Curup, the Mathematics Tadris IAIN is required to be able to organize tadris and teaching in the field of Mathematics Tadris professionally in order to produce educators in the field of Mathematics Tadris who have high morality and are able to compete in the world of tadris. To realize the Islamic, professional, and competitive mathematics teacher is not an easy thing for Mathematics Tadris. Many challenges and obstacles will be felt Mathematics Tadris to achieve it all. Therefore, it is necessary to analyze the strengths and weaknesses of Mathematics Tadris study programs to anticipate challenges and create opportunities using SWOT. The main sources in data collection are plt. Head of Tarbiyah Department, plt. Head of Mathematics Tadris, Staff of Mathematics Tadris, lecturers at IAIN Curup, and students of Mathematics Tadris IAIN Curup. Strategies undertaken to realize Islamic, professional, and competitive teachers include the development of Islamic teaching materials that are integrated with Islam, linking them with the holy verses of the Quran and Hadith; instill character values to students such as a sense of responsibility and sincerity in completing assignments given by lecturers, independent, honest, and disciplined; give an example to students by greeting and being friendly to students and being fair; establish good relationships with students; be a good example in social life; creating lectures that are full of warmth and fun; provide an objective assessment of students and improve student scientific competence, especially in mathematical science.